The Role of Principals of Public Secondary Schools in Jordan in Enhancing Environmental Citizenship: A Proposed Educational Administrative Guide - Rateb Al-So'ud; Safa Bani Hamdan (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to propose an educational administrative guide to enhance the role of public high school principals in Jordan in the field of environmental citizenship. The study used a survey method that is descriptive and evolutionary. The sample consisted of (123) principals and (598) teachers for the academic year 2017/2018. A questionnaire was developed that consisted of (49) items divided into three fields: participation and personal responsibility towards the environment, environmental justice and environmental awareness. The questionnaire was used following ensuring its validity and reliability. The study results showed that the degree of practice of public high school principals in Jordan for environmental citizenship was moderate. In light of the results, a proposed educational administrative guide was developed to enhance the role of public high school principals in Jordan in the field of environmental citizenship. which included three dimensions: air pollution, water pollution, and depletion of environmental resources. The study recommends the Ministry of Education to approve and implement the proposed guide with the schools' principals to enhance the environmental citizenship among their students.